2007
DOI: 10.1016/j.csda.2006.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Quintile stratification based on a misspecified propensity score in longitudinal treatment effectiveness analyses of ordinal doses

Abstract: SummaryThe propensity adjustment provides a strategy to reduce the bias in treatment effectiveness analyses that compare non-equivalent groups such as seen in observational studies (Rosenbaum and Rubin, 1983). The objective of this simulation study is to examine the effect of omitting confounding variables from the propensity score on the quintile-stratified propensity adjustment in a longitudinal study. The primary focus was the impact of a misspecified propensity score on bias. Three features of the omitted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…Previous simulation studies have addressed different questions concerning the choice of the variables to be included in the PS model, such as the effect of omitting confounding variables when using quintile-stratified propensity adjustment in longitudinal studies [27], or the relative performances of PS models when including variables related to treatment allocation, variables related to outcome or all variables related to either outcome or treatment or neither [28]. However, data concerning appropriate PS models when dealing with limited sample sizes are still lacking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous simulation studies have addressed different questions concerning the choice of the variables to be included in the PS model, such as the effect of omitting confounding variables when using quintile-stratified propensity adjustment in longitudinal studies [27], or the relative performances of PS models when including variables related to treatment allocation, variables related to outcome or all variables related to either outcome or treatment or neither [28]. However, data concerning appropriate PS models when dealing with limited sample sizes are still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, while it is usually recommended [17-19] to include in the PS model all the potential confounders, this could lead to over parameterized PS models when the number of treated is limited. On the other hand, it has been previously reported that PS model misspecification could highly influence the estimation [25,27]. Therefore, in the context of small sample sizes, one might consider preferable to apply some variable selection procedure, but it seems crucial to adequately choose those variables to be included in the PS model.…”
Section: Discussionmentioning
confidence: 99%
“…However, the propensity adjustment removes bias related only to variables included in the model and there may be residual confounding from variables related to clinical status or treatments not included, such as anticonvulsants or sedatives. 43,44 Several variables of clinical interest, such as anxiety and psychosis, could not be captured on all participants at the beginning of treatment interval. The assessments for severity of mood symptotm and treatments received were carried out annually and semiannually and have the potential for recall bias.…”
Section: Discussionmentioning
confidence: 99%
“…Yet we acknowledge that the assumption cannot be verified because unmeasured confounding variables, by their very nature, are not in our data set and that a misspecified propensity model can yield biased results. 2627 …”
Section: Discussionmentioning
confidence: 99%